Impact assessment of non-indigenous jellyfish species on the estuarine community dynamic: a model of medusa phase - Muha, Teja Petra (2019)
Non-indigenous jellyfish species (NIJS) Blackforida virginica have recently been introduced to the Guadiana Estuary. A modelling approach was used for the assessment of the species-specific impact on the native community, during the medusa phase. The novel interactions between NIJS and the native community are assessed through biomass variation including hydrodynamic and climatic variables. Sensitivity analysis shows that both native species, as well as NIJS highly depend on the water discharge regime, nutrient contribution and the amount of detritus production. Abiotic factors such as the Northern Atlantic Oscillation, water discharge, nutrient load and detritus production are the most influential factors for the dynamics of the estuarine ecosystem demonstrated by the model. Low water discharge and low nutrient retention rate appear to be the most favourable conditions for B. virginica. The species is a non-selective predator able to integrate into the system effectively and has caused a decrease in the biomass of other organisms in the estuarine ecosystem throughout the summer after dam removal. The B. virginica significant impact can be evaluated only when the jellyfish detritus food pathway is involved. The B. virginica predatory impact potential, as well as food preference, appears to be the most influential factors for the overall biomass variation. On the contrary, winter freshwater pulses reduce the survival rate of jellyfish polyps which results in a decrease of medusa during summer. The model presents a strong ecohydrology movement where the fluctuation of organism biomass strongly depends on the hydrological conditions including the amount of nutrient load.